Comparison of Three Methods for Preparation of Autologous Cells for Use in Cell Therapy of Chronic Limb-Threatening Ischemia in People with Diabetes - Husakova, Jitka; Bem, Robert; Jirkovska, Alexandra; Nemcova, Andrea; Fejfarova, Vladimira; Sutoris, Karol; Kahle, Michal; Jude, Edward B; Dubsky, Michal (The international journal of lower extremity wounds, 2025)
Autologous cell therapy (ACT) is a new therapeutic approach for diabetic patients with no-option chronic limb-threatening ischemia (NO-CLTI). The aim of our study was to quantify cell populations of cell therapy products (CTPs) obtained by three different isolation methods and to correlate their numbers with changes in transcutaneous oxygen pressure (TcPO2). CTPs were separated either from stimulated peripheral blood (PB) (n = 11) or harvested from bone marrow (BM) processed either by Harvest SmartPReP2 (n = 50) or sedimented with succinate gelatin (n = 29). The clinical effect was evaluated by the change in TcPO2 after 1, 3 and 6 months. TcPO2 increased significantly in all three methods at each time point in comparison with baseline values (p < .01) with no significant difference among them. There was no correlation between the change in TcPO2 and the size of injected cell populations. We only observed a weak correlation between the number of injected white blood cells (WBC) and an increase in TcPO2 at 1 and 3 months. Our study showed that all three isolation methods of ACT were similarly relatively efficient in the treatment of NO-CLTI. We observed no correlation of TcPO2 increase with the number of injected monocytes, lymphocytes or CD34+. We observed a weak correlation between TcPO2 increase and the number of injected WBCs.
Keywords: výsledek terapie; Male; Chronic Limb-Threatening Ischemia; ischemie; Aged; mužské pohlaví; senioři; Ischemia; autologní transplantace; Treatment Outcome; buněčná a tkáňová terapie; lidé; ženské pohlaví; Cell- and Tissue-Based Therapy; Humans; transkutánní měření krevních plynů; Transplantation, Autologous; chronická kritická ischemie končetin; Female; Blood Gas Monitoring, Transcutaneous; lidé středního věku; Middle Aged